No place for saints: mobs and Mormons in Jacksonian America - Jortner, Adam Joseph (Witness to history, 2021)
"This is a history of the first decade of Mormonism, beginning with the discovery of the Book of Mormon in 1827 and ending with the so-called Mormon War of 1838, which resulted in the expulsion of Mormons from the state of Missouri"--